SIMILARITIES AND DIFFERENCES OF TENSE IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - LATIPOVA FAYYOZA (TADQIQOTLAR.UZ, 2024)
This study examines the similarities and differences in the tense systems of the English and Uzbek languages. English is an Indo-European language, while Uzbek belongs to the Turkic language family. Despite their linguistic differences, both languages have developed complex tense systems to express time-related information. The analysis reveals that both English and Uzbek have past, present, and future tenses. However, Uzbek has a richer tense system, with additional distinctions such as the witnessed past, non-witnessed past, and reported past. Additionally, Uzbek tenses are formed through a combination of verbal suffixes, whereas English relies more on auxiliary verbs.The paper discusses how these language-specific tense constructions impact the way speakers of English and Uzbek convey temporal information, as well as the pragmatic nuances associated with the different tense forms. It also highlights the challenges language learners may face when transitioning between the tense systems of these two languages.The findings contribute to the broader understanding of cross-linguistic variations in grammatical structures and have implications for language teaching, translation, and comparative linguistics.